A neurophysiological approach to the complex organisation of the spine: F-wave duration and the cutaneous silent period in restless legs syndrome - İŞAK, BARIŞ; ULUÇ, KAYIHAN; AĞAN YILDIRIM, KADRİYE; TANRIDAĞ, TÜLİN (ELSEVIER IRELAND LTD, 2011)
Objective: It is generally accepted that F-wave duration (FWD) and the cutaneous silent period (CSP) are influenced by diminished central inhibition. The aim of this study was to diagnose patients of restless legs syndrome (RLS) with the help of FWD and/or CSP parameters. Methods: In all, 24 patients with primary RLS were compared with 31 age-and sex-matched controls. The participants were evaluated based on nerve conduction study (NCS), F-wave parameters (minimum, maximum and mean latency; chronodispersion, persistence and duration; and the ratio of the mean FWD to compound muscle action potential (CMAP) duration), CSP (latency, duration and the ratio of lower-extremity (LE) to upper-extremity (UE) duration that is, silent period ratio (SPR)), the expiration to inspiration ratio (E/I) and sympathetic skin response (SSR). Results: There were not any significant differences in NCS, E/I or SSR between the patients and controls. However, FWD was prolonged (P < 0.0001 for UE and LE) and FWD/CMAP duration was increased in upper and lower extremities (P < 0.001 for UE and P < 0.0001 for LE). Further, CSP latencies in UE (P = 0.030) and LE (P < 0.001) were prolonged, and CSP duration and SPR were significantly reduced in the patient group (P < 0.0001). Conclusions: As both NCS and autonomic test results were in the normal range, abnormalities in FWD and CSP parameters were attributed to the dysfunction of different interneuron groups in the spine. Significance: The use of FWD and CSP could aid in the diagnosis of RLS patients in whom conventional electrophysiological procedures are ineffective. (C) 2010 International Federation of Clinical Neurophysiology. Published by Elsevier Ireland Ltd. All rights reserved.
Keywords: Restless legs syndrome; F-wave; Cutaneous silent period; Interneuron; SURAL NERVE-CONDUCTION; CLINICAL UTILITY; EXCITABILITY; SYSTEM; RAT; MOVEMENTS; DOPAMINE; INTERNEURONS; INHIBITION; NEUROPATHY